SQUARE OF LEAF SURFACE OF PEA DEPENDING ON TECHNOLOGICAL TECHNIQUES IN THE CONDITIONS OF THE WESTERN FOREST STEPPE - Khmelianchyshyn, Yurii; Nebaba Кateryna (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Active leaf activity,stipules and whiskers of allows the development of production processes in plants and significantly affects the intensity of photosynthesis during the growing season. Optimal growth and development of plants, that affects the accumulation of organic matter and level of supply of mineral nutrients also depents of leaf surface square. The results of researches where was learned the square of leaf surface and its influence to yield of modern varieties of pea depending on different doses of mineral fertilizers and growth regulators in the conditions of the western forest steppe are presented in the article . Experimental part was conducted during 2016-2018 on the research field of the Training and Production Center "Podillya" PDU. The soil of the research field – is chernozem chernic, deep глибокий low humus, heavy loam on woody loams. It’s set out, that square of leaf surface of pea varieties Gotovsky, Chekbek and Fargus depented on varietal features of culture and technological measures which were applied in the reserch. Spraying of crops of PlantaPeg, Emistim C and Vimpel growth regulators in microstages ВВСН 55-65 has provided active formation of the leaf surface area of pea plants. During the growing season the square of assimilation surface has grown and reached досягла maximum values in microstages ВВСН 60-65. The actions of the PlantaPeg regulator in plants of the Gotovsky variety the aquare og leaf surface fluctuateв from 176,4 til 330,2 square centimeters per plant, Chekbek – from 218,3 till 394,5 square centimeters per plant and Fargus – from 167,2 till 317,0 square centimeters per plant. In plants sprayed with Emistim C, the leaf surface area increased from 190.6 to 407.5 cm2 / plant, depending on the varieties, but the growth regulator Vimpel worked best on all studied varieties of peas - sowing ranged from 218.0 to 415.1 cm2 / plant.